2017
DOI: 10.1371/journal.pone.0179052
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infection and blood food sources of phlebotomines in an area of Brazil endemic for visceral and tegumentary leishmaniasis

Abstract: The aims of the study were to determine the blood feeding preferences of sandflies and to identify species of Leishmania that infected phlebotomines in Caxias, Maranhão, Brazil, an area that is highly endemic for leishmaniasis. Sandflies were captured in light traps located in the peridomiciliary environments of randomly selected houses in urban and rural settings between 1800 and 0600 hours on new moon days between March 2013 and February 2015. DNA extracts from 982 engorged female sandflies were submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…This is similar to the results of some studies in Old World settings that found frequencies of between 0.3% to 7.0% in females that had both fed and not fed [ 44 , 45 ]. Our result is in concordance with the findings of several previous studies of vectors in different areas of Brazil where CL is endemic, which described Leishmania frequencies of between 3.4% and 8.1% [ 42 , 46 48 ]. In concordance with Souza-Ferreira et al .…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to the results of some studies in Old World settings that found frequencies of between 0.3% to 7.0% in females that had both fed and not fed [ 44 , 45 ]. Our result is in concordance with the findings of several previous studies of vectors in different areas of Brazil where CL is endemic, which described Leishmania frequencies of between 3.4% and 8.1% [ 42 , 46 48 ]. In concordance with Souza-Ferreira et al .…”
Section: Discussionsupporting
confidence: 93%
“…Shelters installed without the necessary hygiene and protection are important factors that justify the greater abundance of sand flies in the backyards of houses (Pereira‐Filho et al 2015, Bandeira et al 2017). In these shelters, sand flies were found containing the blood of domestic animals, including dogs, pigs, horses, chickens, and synanthropic rodents and marsupials (Dias et al 2003, Oliveira‐Pereira et al 2008, Fonteles et al 2009, Guimarães‐e‐Silva et al 2017, Pereira‐Filho et al 2018, Fonteles et al 2018). However, the peri‐domicile sites where sand flies breed should be studied in detail with specific methodologies, as immatures are not easy to find.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a great species richness and abundance of sand flies in the peri‐domicile environments of several municipalities in the State of Maranhão (Silva et al 2010, 2012, 2015, Campos et al 2013, Rebêlo et al 2019). Some of these species are infected with different Leishmania species (Guimarães‐e‐Silva et al 2017, Pereira‐Filho et al 2018, Fonteles et al 2018). In these areas, cases of cutaneous and visceral leishmaniasis have been reported (Martins et al 2004, Costa et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although cattle were found to provide only 0.6% of the blood source for Lutzomyia sp. in a rural area in Maranhão, Brazil, it was noted that this was nonetheless a valid blood source, thus providing a reminder that sand flies have opportunistic feeding habits (GUIMARÃES-E-SILVA et al, 2017). On the other hand, a study in Ethiopia showed that cattle were the second most preferred host of Phlebotomus orientalis (GEBRESILASSIE et al, 2015).…”
Section: Introductionmentioning
confidence: 99%